2014
DOI: 10.1002/ppsc.201400219
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Graphene Quantum Dots for Fluorescence Bioimaging from Cells through Tissues to Animals

Abstract: 515wileyonlinelibrary.com www.particle-journal.com www.MaterialsViews.com REVIEWGraphene quantum dots (GQDs) have attracted tremendous attention in recent years. In this review, the recent developments are summarized in the synthesis, edge functionalization, and cyctotoxicity of GQDs, followed by presenting a focused overview on their current applications for in vitro fl uorescence imaging in cells and tissues as well as in vivo macroscopic and microscopic imaging in animals. Challenges and opportunities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 77 publications
0
72
0
Order By: Relevance
“…For instance, there could be an interplay of emission from the CDs core and surface states 20,48 or by variation in degree of the surface oxidation of constituting fluorescent groups 41 . For instance, there could be an interplay of emission from the CDs core and surface states 20,48 or by variation in degree of the surface oxidation of constituting fluorescent groups 41 .…”
Section: The Lifetime Heterogeneity and Its Absence On A Single-partimentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there could be an interplay of emission from the CDs core and surface states 20,48 or by variation in degree of the surface oxidation of constituting fluorescent groups 41 . For instance, there could be an interplay of emission from the CDs core and surface states 20,48 or by variation in degree of the surface oxidation of constituting fluorescent groups 41 .…”
Section: The Lifetime Heterogeneity and Its Absence On A Single-partimentioning
confidence: 99%
“…Tremendous attention is attributed to biological imaging 48,86 . Tremendous attention is attributed to biological imaging 48,86 .…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Recently, there are also several reports about GQDs' bottom-up synthesis using citric acid or other non-aromatic molecules through hydrothermal process, 19 In addition to surface group removing, the bad gap engineering is very critical for modulating of PL emission wavelengths (λ em ) and enhancing the PL efficiency (quantum yield, φ). [21][22][23][24][25][26][27][28] In theory, a pure band gap PL process will bring very good control on λ em and φ. It has been reported that by the negative induction effect of heteroatoms (such as F and N) with high electronegativity, the band gap of GQDs or carbon dots will be broadened effectively.…”
mentioning
confidence: 99%
“…Carbon nanodots (CDs), including CQDs and graphene quantum dots are emerged as the most recent members in the NC family and have generated enormous excitement due to their unique structure and properties . Generally, the 0D CDs exhibit a size below 10 nm with abundant functional groups on the surface.…”
Section: Nife Ldh/nc Hybrid Catalysts For Oermentioning
confidence: 99%